An exploratory analysis of differences in serum protein expression by sex in patients with systemic sclerosis associated interstitial lung disease - Giuliana Cerro-Chiang; Matthew Ayres; Alejandro Rivas; Sarah J. Parker; Mitra Mastali; Peter Chen; Jennifer E. Van Eyk; Paul J. Wolters; Francesco Boin; Tanzira Zaman (BMC Pulmonary Medicine)
Abstract Background Systemic sclerosis (SSc) is a rare connective tissue disease, frequently affecting the skin, lungs, and pulmonary vasculature. Approximately 30–50% of SSc patients develop interstitial lung disease (SSc-ILD), with 30–35% of related deaths attributed to it. Even though men are less likely to develop systemic sclerosis, they have a higher incidence of SSc-ILD than women, and they tend to develop it at a younger age with a higher mortality rate. Sex differences in protein expression in the blood of patients with SSc-ILD have not been reported to date. We aimed to identify sex differences in serum protein expression between men and women with SSc-ILD. Methods Serum specimens of patients with SSc-ILD underwent dual mass spectrometry (LC-MS/MS) analysis. The association between protein biomarkers and sex was assessed through logistic regression. Time to event analysis was performed to determine any differences in the time to FVC decline of > 5% and the proportion of subjects who experienced FVC decline of > 5% by sex over the total period of observation. The association between biomarkers and sex was assessed through logistic regression. For proteins that were dichotomized, chi-squared testing was used. Multivariable regression models adjusting for meaningful clinical variables were also performed. Results The cohort consisted of 211 subjects, 162 women and 47 men with a median follow-up of 3.52 years. No significant sex differences were found in the time to FVC decline of > 5% or > 10%. Among the 704 proteins identified, forty differed significantly between sexes. After adjusting for multiple testing, Autotaxin remained significantly higher in women. Autotaxin, known to activate lysophosphatidic acid and promote fibrosis, suggests a potential role in modulating fibrotic processes in SSc-ILD. Conclusions This study is the first to report sex-specific serum protein differences in patients with SSc-ILD, with Autotaxin remaining significantly different after adjusting for multiple testing. These proteins could influence disease progression and treatment response and underscore the importance of personalized therapeutic strategies and further research into sex-related molecular pathways in SSc-ILD. Clinical trial number Not applicable.